FACTORS INFLUENCING CUSTOMERS’ ACCEPTANCE OF INTERNET SERVICES IN IRAN - Khodayari, Samira; Hatami, Hojat; Ahmadian, Sahar (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2024)
The purpose of this research is to investigate the factors influencing customers’ acceptance of internet services in sports electronic stores in Iran, Tehran Province. In this research, it will highlight the role of content marketing, trust, innovation, website design, ease of use, and evaluation of the company's internet services. In this way, managers can improve the acceptance of such services of the company and provide the basis for making profit and increasing their market share. This research is an applied research, in terms of the data collection method, it is a descriptive survey research and the data collection tool is a standard questionnaire. The population of this research includes managers and employees of selected sports equipment stores in Tehran, for statistical analysis. SPSS software is used for data analysis. The research finding showed that the variable of content marketing, trust, innovation, website design, ease of use, and attitude has a positive effect on company's internet services acceptance. The findings of the research may be used for customers’ acceptance of internet services in sports equipment stores in Iran.